Development of higher order thinking skills based accounting E-LKPD at SMK Negeri 5 Palembang - Dea Husnul Khotimah Khotimah; Neta Dian Lestari; Nova Pratiwi (Institute of Computer Science (IOCS), 2023)
This research is a research and development (R&D) HOTS-based accounting E-LKPD teaching material. This re search uses the ADDIE research model which has five stages, namely analysis, design, development, implementation, and evaluation. The results showed that the development of the accounting E-LKPD was declared efficient according to the results of media, material and language experts with an average of 84.29%. In terms of practicality, the one-to-one test averaged 89.91%, the criteria were very valid, and in the Small Group test, with an average result of 93.06%, the criteria were very valid. the average result is 73.33% good criteria and the post-test with an average result of 86.13% is very good criteria. So that there was an increase of 12.8% in the learning outcomes of class X AKL 2 SMK Negeri 5 Palembang. Effective when conducting research by obtaining an average observation of 88.84% very active criterion.